A randomized pilot study of L-arginine infusion in severe falciparum malaria: preliminary safety, efficacy and pharmacokinetics. - Tsin W Yeo; Daniel A Lampah; Indri Rooslamiati; Retno Gitawati; Emiliana Tjitra; Enny Kenangalem; Ric N Price; Stephen B Duffull; Nicholas M Anstey (PLoS ONE)
Background Decreased nitric oxide (NO) and hypoargininemia are associated with severe falciparum malaria and may contribute to severe disease. Intravenous L-arginine increases endothelial NO in moderately-severe malaria (MSM) without adverse effects. The safety, efficacy and pharmacokinetics of L-arginine or other agents to improve NO bioavailability in severe malaria have not been assessed. Methods In an open-label pilot study of L-arginine in adults with severe malaria (ARGISM-1 Study), patients were randomized to 12 g L-arginine hydrochloride or saline over 8 hours together with intravenous artesunate. Vital signs, selected biochemical measures (including blood lactate and L-arginine) and endothelial NO bioavailability (using reactive hyperemia peripheral arterial tonometry [RH-PAT]) were assessed serially. Pharmacokinetic analyses of L-arginine concentrations were performed using NONMEM. Results Six patients received L-arginine and two saline infusions. There were no deaths in either group. There were no changes in mean systolic (SBP) and diastolic blood pressure (DBP) or other vital signs with L-arginine, although a transient but clinically unimportant mean maximal decrease in SBP of 14 mmHg was noted. No significant changes in mean potassium, glucose, bicarbonate, or pH were seen, with transient mean maximal increases in plasma potassium of 0.3 mmol/L, and mean maximal decreases in blood glucose of 0.8 mmol/L and bicarbonate of 2.3 mEq/L following L-arginine administration. There was no effect on lactate clearance or RH-PAT index. Pharmacokinetic modelling (n = 4) showed L-arginine concentrations 40% lower than predicted from models developed in MSM. Conclusion In the first clinical trial of an adjunctive treatment aimed at increasing NO bioavailability in severe malaria, L-arginine infused at 12 g over 8 hours was safe, but did not improve lactate clearance or endothelial NO bioavailability. Future studies may require increased doses of L-arginine. Trial registration ClinicalTrials.gov NCT00616304.